An evaluation of small-scale piggeries in Limpopo Province, South Africa - Manchidi, M. J. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Animal Sciences. Livestock Industry Management: Pig Science))--University of Stellenbosch, 2009.